(untitled) - Orwel, George (Hoboken, N.J., 2006)
Analyze how the falling production and rising demand of oil has enabled savvy companies and investment banks to cash in with Black Gold. You'll find investment suggestions -- from ETFs and energy futures to hedge funds -- that will allow you to reap substantial profits from current and future situations as well as short human-interest stories that illustrate every issue discussed. You'll also find a timeframe for the peak of oil production -- one that is more realistic and gaining acceptance with both scientists and economists. Drawing on historical background, current issues, and expectations of the energy road ahead, Black Gold offers information you'll appreciate and understand so you can make the most of a market poised to grow exponentially in the years ahead.
Keywords: Dầu mỏ,Petroleum industry and trade,Petroleum products,Petroleum,Ngành công nghiệp dầu khí và thương mại,Sản phẩm dầu mỏ; Sự phát minh,Prices,Investment,Giá